2022
DOI: 10.37917/ijeee.18.1.15
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of COIVD-19 Cases Classification Based on Machine Learning Approaches

Abstract: COVID-19 emerged in 2019 in china, the worldwide spread rapidly, and caused many injuries and deaths among humans. Accurate and early detection of COVID-19 can ensure the long-term survival of patients and help prohibit the spread of the epidemic. COVID-19 case classification techniques help health organizations quickly identify and treat severe cases. Algorithms of classification are one the essential matters for forecasting and making decisions to assist the diagnosis, early identification of COVID-19, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Atiyah et al 68 showed that the Stochastic Gradient Descent (SGD) algorithm performed best among the classification algorithms (LR, GNB, RF, SGD, KNN, SVM, XGBoost, and DT) used based on ICU labeling, and KNN showed the worst performance.…”
Section: Discussionmentioning
confidence: 99%
“…Atiyah et al 68 showed that the Stochastic Gradient Descent (SGD) algorithm performed best among the classification algorithms (LR, GNB, RF, SGD, KNN, SVM, XGBoost, and DT) used based on ICU labeling, and KNN showed the worst performance.…”
Section: Discussionmentioning
confidence: 99%